"Rag-Doll" Test for Seed Germination - Carrol G. Chambliss (Editor) (EDIS)
This document is SS-AGR-179, one of a series of the Agronomy Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. First published 1999. Revised August 2002.